2022
DOI: 10.3390/coatings12101478
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Steel Fiber of Rigid Pavements: A 3D Finite Element and Parametric Analysis

Abstract: Rigid pavements have high compressive strength and low flexural strength due to the brittleness of concrete. This leads to the formation of cracks easily under the applied loads of vehicles; therefore, the design of concrete pavements usually leads to an increase in the high thicknesses. Hybrid steel fibers are used in concrete to increase flexural strength and minimize crack formation. Using concrete with steel fibers in pavements reduces the required concrete thickness. In recent decades, the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A theoretical equation was proposed for predicting the ultimate load of the strengthened slabs. Al Harki et al [29] developed a finite element model with tandem-axle dual tire loading to assess the influence of hybrid steel fiber on the behavior of rigid pavements. They concluded that hybrid fiber reinforcement greatly enhanced the strength and flexibility of the pavements.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical equation was proposed for predicting the ultimate load of the strengthened slabs. Al Harki et al [29] developed a finite element model with tandem-axle dual tire loading to assess the influence of hybrid steel fiber on the behavior of rigid pavements. They concluded that hybrid fiber reinforcement greatly enhanced the strength and flexibility of the pavements.…”
Section: Introductionmentioning
confidence: 99%